Case report: Rechallenge with EGFR–TKIs after immunotherapy in EGFR–mutated non–small cell lung cancer with leptomeningeal metastasis - Qian, Chunfa; Zhang, Yuhai; Cheng, Wanwan; Zhang, Qingchao; Li, Mengzhen; Fang, Shencun (Frontiers in Oncology, 2022)
Epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) rechallenge after PD-1 blockade failure was an effective therapy for non-small cell lung cancer (NSCLC) patients with resistance to EGFR-TKIs. The third-generation TKIs, like osimertinib and furmonertinib, can get higher concentration and penetration into the cerebrospinal fluid (CSF) and exhibit a beneficial effect in NSCLC patients with leptomeningeal metastases (LM) harboring sensitive EGFR mutation. Here, we report two stage IV pulmonary adenocarcinoma patients with LM harboring an EGFR L858R mutation benefit from the third-generation EGFR-TKIs rechallenge after immune checkpoint inhibitor (ICI) and anti-angiogenic agents combination therapy. Complete response (CR) or partial response (PR) of central nervous system (CNS) response were achieved immediately after the administration of the furmonertinib and osimertinib. We conducted next-generation sequencing (NGS) and mIHC to elucidate the evolution of driver mutations and immune microenvironment. In conclusion, these cases might provide a therapeutic strategy in further clinical practice. More research was needed to elucidate the resistance mechanisms and improve current treatment strategies in EGFR-mutated patients with LM.